Passive zooplankton community in dry littoral sediment: Reservoir of diversity and potential source of dispersal in a subtropical floodplain lake of the Middle Paraná River (Santa Fe, Argentina) - Battauz, Yamila Soledad (2014)
During the low water or contraction phase, the Parana floodplain lakes show a marginal area with the littoral sediments exposed to the air. They were studied as “resting stage bank” and potential zooplankton diversity storage as well as a source of propagules for exozoochoric dispersal by terrestrial and semiaquatic vectors, mainly birds. The aims of the study were to analyze (i) specific composition of the zooplankton hatchling assemblage, (ii) time and hatching pattern of each species, (iii) similarities and differences between hatchlings and active assemblages, (iv) assessment of the habitat membership (limnetic/littoral) of hatched species. Sediment samples were taken from three sites of a representative floodplain lake of Paraná River and hatching experiments were conducted under laboratory conditions at 25°C for 90 days. Twenty-seven species of rotifers and four of cladocerans hatched in the laboratory. Hatchlings (7097 specimens) were recorded (92.4% rotifers, 7.6% cladocerans). The number of hatched species increased significantly from day 4 to day 30, showing oscillating trends and then began to decrease until day 90. Thirty percent of hatched species were unrecorded for the lake, and 12% species were new records for Argentina. Seventy-seven percent of the hatched species were littoral in habit.